2016
DOI: 10.19044/esj.2016.v12n35p171
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Quality of Life of Jordanian Children and Adolescents with End Stage Renal Disease Receiving Hemodialysis

Abstract: Background: Depression is a common psychosocial problem that negatively affects the lives and relationships of school-age children, adolescents, and adults both in private and public. Purpose: To explore the psychosocial well-being among Jordanian schoolage children and adolescents who are complaining of end stage renal disease (ESRD) undergoing hemodialysis. Method and Design: The study was carried out using a descriptive crosssectional correlation design. A convenient sample of 121 school-age children and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…End-stage renal disease (ESRD) is a growing public health problem with significant physiological, psychological and socio-economic implications for the individual, family and the community [1, 2]. Despite advances in technology and medical care, it remains a serious and life-threatening illness with a very high mortality rate and low quality of life [35]. Studies revealed the world wide incidence and prevalence of ESRD is increasing and it is projected that by 2020 the number of patients with ESRD will rise by nearly 60% in comparison with that of 2005 [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…End-stage renal disease (ESRD) is a growing public health problem with significant physiological, psychological and socio-economic implications for the individual, family and the community [1, 2]. Despite advances in technology and medical care, it remains a serious and life-threatening illness with a very high mortality rate and low quality of life [35]. Studies revealed the world wide incidence and prevalence of ESRD is increasing and it is projected that by 2020 the number of patients with ESRD will rise by nearly 60% in comparison with that of 2005 [6, 7].…”
Section: Introductionmentioning
confidence: 99%